The Relationship Between Sense of Community And Agreeableness with Prosocial Behavior among Member of Young On Top (YOT) - Ariska Tri Devi; Munawir Yusuf; Hardjono Hardjono (Journal of ICSAR, 2017)
Helping behavior that benefits others or society in general called as prosocial behavior. Prosocial behavior refers to voluntary actions that are intended to help and give benefit for another individual or group. Prosocial behavior in the individual in a community or organization can be affected by sense of community and agreeableness. The aim of this study is to determine: (1) the relationship between sense of community and agreeableness with prosocial behavior, (2) the relationship between sense of community with prosocial behavior, and (3) the relationship between agreeableness with prosocial behavior among member of Young On Top (YOT).The population of this study is member of Young On Top (YOT) region Joglosemar-Jatim 2015 which is divided in six cities, those are in Solo, Semarang, Jogja, Malang, Jember, and Surabaya. Sampling used population studies or census by using the entire population consisting 162 members. Instrument in this study used prosocial behavior scale, sense of community scale, and agreeableness scale using Indonesian version of BFI. Multiple regression analysis was used for examining the first hypothesis, and partial correlation test for examining the second and the third hypothesis.The result of this study showed that there was a significant positive correlation between sense of community and agreeableness with prosocial behavior among member of Young On Top (YOT) (F-test = 100,875; p < 0,05; and R = 0,784). Partially, the result shows the significant positive correlation between sense of community and prosocial behavior (r = 0,660; p < 0,05), and there is significant positive correlation between agreeableness and prosocial behavior (r = 0,244; p < 0,05). The value of R2 in this study is 0,559 or 55,9% which was of effective contribution of sense of community towards prosocial behavior with amount 47,26% and effective contribution of agreeableness towards prosocial behavior with amount 8,67%.